Pengaruh Jumlah Uang Beredar dan Inflasi terhadap Pertumbuhan Ekonomi Indonesia (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to investigate the impact of money supply and inflation on economic growth in Indonesia. The research adopts a quantitative approach, utilizing secondary data sourced from relevant financial reports and statistical agencies. Multiple linear regression analysis is employed to evaluate the relationship between the independent variables (money supply and inflation) and the dependent variable (economic growth). The data is processed using SPSS (Statistical Package for the Social Sciences) version 25. The findings indicate that the money supply has a significant positive effect on Indonesia's economic growth, suggesting that an increase in money supply can stimulate economic activity. On the other hand, inflation is found to have a positive but insignificant effect on economic growth. The results of the hypothesis testing indicate that, when considered simultaneously, both money supply and inflation contribute to economic growth, but the impact of inflation is less pronounced. These findings have important implications for policymakers in Indonesia, suggesting that managing the money supply is crucial for fostering economic growth, while inflation control remains important but less directly impactful in the short term.